iPSC-Derived Gaucher Macrophages Display Growth Impairment and Activation of Inflammation-Related Cell Death - Daria Messelodi; Salvatore Nicola Bertuccio; Valentina Indio; Silvia Strocchi; Alberto Taddia; Salvatore Serravalle; Jessica Bandini; Annalisa Astolfi; Andrea Pession (Cells, 2021)
Gaucher disease is a lysosomal storage disorder characterized by β-glucosidase enzyme deficiency and substrate accumulation, especially in cells of the reticuloendothelial system. Typical features of the disease are the unrestrained activation of inflammatory mechanisms, whose molecular pathways are still unclear. To investigate biological mechanisms underlying the macrophage activation in GD, we derived iPSCs from a healthy donor and a GD patient line and differentiated them into hematopoietic progenitors. While GD iPSCs are able to efficiently give rise to CD33+/CD45+ myeloid progenitors, the maturation towards the CD14+/CD163+ monocyte/macrophages fate resulted enhanced in the GD lines, that in addition displayed a decreased growth potential compared to control cells either in semisolid or in liquid culture. The GD lines growth impairment was associated with a significant upregulation of RIPK3 and MLKL, two key effectors of necroptosis, the inflammation related cell death pathway. The activation of necroptosis, which has already been linked to neuronopathic GD, may play a role in the disease proinflammatory condition and in the identified cell growth defects. Understanding the GD macrophage role in the alteration of mechanisms linked to cellular metabolism imbalance, cell death and inflammation are crucial in identifying new ways to approach the disease.